Empowering Recovery: Women-Specific Interventions and Trauma-Informed Care in Holistic Drug Addiction Rehabilitation - Seymour , Lipton; Cattaneo, Kreiner Azhar; Miglioretti, Miglioretti (Intitute of Computer Science (IOCS), 2023)
This research explores the effectiveness of social service models tailored specifically for women within drug addiction recovery centers. A mixed-methods approach was employed, incorporating qualitative interviews and quantitative surveys to evaluate the impact of diverse interventions on women's recovery journeys. The study involved purposeful sampling of recovery centers offering specialized programs for women. Qualitative data from interviews and focus groups illuminated the experiences and perceptions of women in recovery, highlighting the significance of trauma-informed care, gender-sensitive approaches, and empowerment-focused interventions. Quantitative analysis revealed promising outcomes, showcasing the positive impact of tailored interventions on treatment retention rates, reduced relapse occurrences, and improvements in mental health indicators among participants. Findings indicated the success of trauma-informed care and gender-specific interventions in addressing women's unique needs, fostering trust, empowerment, and holistic healing. Challenges in resource allocation, implementation quality, and inclusivity were identified, providing opportunities for policy changes, enhanced training, and model refinement. This study contributes insights into the essential components of effective social service models for women in drug addiction recovery centers. Recommendations include the integration of successful components, policy advocacy for funding allocation, and continuous evaluation for ongoing model refinement.